Virtudes socioambientais e as razões capitalistas em empreendimentos capitalistas e de economia social - José Luiz Bica de Mélo; Monika Dowbor (Ciências Sociais Unisinos)
Would the Social Economy enterprises present a set of actions more environmentally sustainable than their capitalist equivalents? Or, has the growing political and social importance of sustainability already left a positive landmark in the business? These questions guided the case study in which we compared the forms of use of natural resources, notably water and soil, contrasting Social Economy enterprises - cooperative producing ecological rice in Rio Grande do Sul State and agroecological consortia based on the production of cotton in Ceará State - with capitalist companies of the same branches of agricultural production. The research conducted through interviews, field observations, and secondary data shows that the environmentally virtuous actions differ by type of enterprise and not by type of product grown, and the social economy organizations, in those cases studied, were effectively more virtuous than the capitalist enterprises.